PERLINDUNGAN HUKUM HAK CIPTA ATAS PROGRAM KOMPUTER MENURUT UNDANG-UNDANG NOMOR 19 TAHUN 2002 TENTANG HAK CIPTA (STUDI KASUS DI KECAMATAN PULAU LAUT UTARA, KABUPATEN KOTABARU) - Raharjo, Dimen; Hawin, H.M. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this research is to determine: (1) the forms of violation of the copyright on computer programmes in the North Pulau Laut, Kotabaru Regency, (2) the forms of protection of computer programs copyright according to Act No. 19 of 2002 about copyright, and (3). The efforts to prevent copyright infringement over the computer program in the North Pulau Laut, Kotabaru Regency. This type of research is research that is normative empirical, namely the kind of research that examines the implementation of the provisions of the positive law and contract, factually in every specific case law in the community in order to achieve the goals that have been determined. The results showed that: (1) the forms of copyright infringement for computer programs in the North Pulau Laut, Kotabaru Regency, among others